2011
DOI: 10.1038/leu.2011.101
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor TNFAIP3 (A20) is frequently deleted in Sézary syndrome

Abstract: Despite recent therapeutic improvements, the prognosis for patients suffering from Sé zary syndrome (SS), a disseminated form of cutaneous T-cell lymphomas, is still poor. We identified bi-and monoallelic deletions of the tumor necrosis factor-ainduced protein 3 gene (TNFAIP3; A20) in a high proportion of SS patients as well as biallelic A20 deletion in the SS-derived cell line SeAx. Furthermore, we demonstrate that inhibition of A20 activates the NF-jB pathway thereby increasing the proliferation of normal T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 27 publications
(34 reference statements)
3
56
0
Order By: Relevance
“…Deletion of the CDKN2A gene at the 9p21 locus (Laharanne et al, 2010;Vermeer et al, 2008) has been confirmed in approximately half of SS patients as reported in other NGS studies, which also have shown that the presence of CDKN2A inactivating mutations in a subset of patients (Choi et al, 2015;Kiel et al, 2015;Wang et al, 2015). Genetic loss at 6q23e27 of TNFAIP3, initially detected in half of SS samples, has been confirmed only in a single NGS study (Braun et al, 2011;Choi et al, 2015). Finally, except when single nucleotide polymorphism array analysis was associated (Wang et al, 2015), most NGS studies, including the one by Prasad et al (2016), have not reported gain of MYC and/or loss of its antagonist MNT, which have been recovered in 76% of patients with SS (Boonk et al, 2016;Vermeer et al, 2008).…”
mentioning
confidence: 76%
“…Deletion of the CDKN2A gene at the 9p21 locus (Laharanne et al, 2010;Vermeer et al, 2008) has been confirmed in approximately half of SS patients as reported in other NGS studies, which also have shown that the presence of CDKN2A inactivating mutations in a subset of patients (Choi et al, 2015;Kiel et al, 2015;Wang et al, 2015). Genetic loss at 6q23e27 of TNFAIP3, initially detected in half of SS samples, has been confirmed only in a single NGS study (Braun et al, 2011;Choi et al, 2015). Finally, except when single nucleotide polymorphism array analysis was associated (Wang et al, 2015), most NGS studies, including the one by Prasad et al (2016), have not reported gain of MYC and/or loss of its antagonist MNT, which have been recovered in 76% of patients with SS (Boonk et al, 2016;Vermeer et al, 2008).…”
mentioning
confidence: 76%
“…A20, a zinc-finger protein, has been found to have an effect on the pathogenesis of multiple cancers, suggesting an oncogenic role. However, deletions, mutations and inactivations of A20 have been identified in several different subtypes of lymphomas, including Hodgkin lymphomas, primary mediastinal B cell lymphomas [21,22], non-Hodgkin lymphomas [23] and Sézary syndrome [24]. These data suggest that A20 may also act as a tumor suppressor in some types of lymphomas.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, bi- and monoallelic A20 deletions in a high proportion of Sezary syndrome patients and a biallelic A20 deletion in the Sezary syndrome-derived cell line SeAx were identified. Furthermore, A20 inhibition activates the NF-κB pathway, thereby increasing the proliferation of normal T-cells [17]. Interestingly, we recently found that there are rare A20 mutations and polymorphisms in T-ALL [25].…”
Section: Introductionmentioning
confidence: 99%